Factors Correlated with Willingness and Compliance to Pay National Health Insurance Premium in Jember Regency - Nazilla Ade Nurlia; Bhisma Murti; Didik Gunawan Tamtomo (Masters Program in Public Health, Sebelas Maret University, 2021)
Background: Fulfillment of premium collectivity is related to willingness and compliance to pay BPJS Kesehatan premiums. Increasing participation in the informal sector is not in line with compliance in paying BPJS Health premiums. This study aims to analyze the influence of factors of willingness and compliance to pay premiums for BPJS Kesehatan independent participants in Jember Regency.Subjects and Method: This was a cross sectional study conducted in 31 sub-districts in Jember Regency, East Java, in July-September 2020. Sampling of 200 BPJS Kesehatan Mandiri participants was conducted using random sampling. The dependent variable is willingness to pay and compliance to pay the BPJS Health premium. The independent variables include education, income, willingness to pay, imitation of the referral group and number of family members. Data were collected using a questionnaire. Data were analyzed using multiple linear regression, multiple logistic regression and path analysis with Stata 16.Results: Factors that affect the willingness to pay are education (b= 45531.18; 95% CI= 35335.1 to 55727.26; p <0.001) and (b= 2.13 units; 95% CI= 1.41 to 2.86; p <0.001), income (b= 17469; 95% CI= 7171.90 to 27766.09; p <0.001), and (b= 1.19; 95% CI= 0.46 to 1.92; p <0.001). Compliance to pay is influenced by the willingness to pay factor (b= 4.19; 95% CI = 2.19 to 8.04; p <0.001) and (b= 0.64; 95% CI= 0.02 to 1.27; p= 0.044) with an average willingness to pay Rp 44,792, imitation of the reference group (b= 2.59; 95% CI = 1.39 to 4.85; p= 0.003) and (b = 0.95; 95% CI = 0.33 to 1.58; p= 0.003) and the number of family members (b= 1.90; 95% CI= 1.02 to 3.56; p= 0.044).Conclusion: Willingness to pay premiums is directly affected by education and income. Compliance with premium payments is directly affected by willingness to pay, imitation of the referral group, and the number of family members.Keywords: willingness to pay, paying compliance, social cognitive theoryCorrespondence: Nazilla Ade Nurlia.Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: nazillaade29@gmail.com. Mobile: +6281230004195.Journal of Health Policy and Management (2021), 06(01): 35-47https://doi.org/10.26911/thejhpm.2021.06.01.04